Effects of catnip (Nepeta cataria L.) and Mexican sunflower (Tithonia diversifolia L.) density on growth, yield, and proximate composition of jute mallow (Corchorus olitorius L.) - О.П. Айоделе; О.А. Алуко; О. Д. Адегбаджу (Plant Varieties Studying and Protection)
Purpose. Jute mallow (Corchorus olitorius L.) is a mucilaginous vegetable and fiber crop cultivated in the tropics, where catnip (Nepeta cataria L.) and Mexican sunflower (Tithonia diversifolia L.) are common weeds. Hence, the study investigated the growth, yield, and nutrient level of jute mallow in weed-free, catnip, and Mexican sunflower environments.